Pengaruh Penggunaan Model Belajar Kooperatif Tipe STAD (Student Teams Achievement Division) Terhadap Hasil Belajar Pendidikan Agama Kristen Pada Siswa Kelas IV SDN No. 233 Inpres Botang - Widiarto Boro Allo (Sekolah Tinggi Teologi Internasional Harvest Tangerang, 2022)
Abstract This research was conducted to obtain a description of how the learning process of Christian Religious Education by using cooperative learning models to improve student learning outcomes in Christian Religious Education class IV SDN No. 233 Botang Presidential Instruction. This study uses quantitative research, with a quasi-experimental research product design with pre-test and post-test control group design. The population in this study were all fourth grade students at SDN No. 233 Inpres Botang for the academic year 2021/2022 with a total of 35 students, while the research sample is the total population. Activities are carried out by providing action or control to the sample. However, before giving the action, first a pre-test was carried out, then after the action was given, a post-test was given to find out whether there was an effect before and after the action was given. Data collection techniques were carried out using observation techniques, tests using questionnaires and documentation. From the research conducted, it was found that the use of the STAD type cooperative learning model significantly improved student learning outcomes, it was seen from the results of data analysis in SPSS, which showed the value of Sig. (2-tailed) of 0.001 < 0.05. Another thing that also shows is the difference or difference in the average value between the pre-test and post-test, or 60.86 – 90.29 = -29.429